Mechanism of the AppABLUF Photocycle Probed by Site-Specific Incorporation of Fluorotyrosine Residues: Effect of the Y21 pKa on the Forward and Reverse Ground-State Reactions - Gil, Agnieszka; Haigney, Allison; Laptenok, Sergey P; Brust, Richard; Lukacs, Andras; Iuliano, James; Jeng, Jessica; Melief, Eduard; Zhao, Rui-Kun; Yoon, EunBin; Clark, Ian; Towrie, Michael; et al. (Journal of the American Chemical Society, 2016)
The transcriptional antirepressor AppA is a blue light using flavin (BLUF) photoreceptor that releases the transcriptional repressor PpsR upon photoexcitation. Light activation of AppA involves changes in a hydrogen-bonding network that surrounds the flavin chromophore on the nanosecond time scale, while the dark state of AppA is then recovered in a light-independent reaction with a dramatically longer half-life of 15 min. Residue Y21, a component of the hydrogen-bonding network, is known to be essential for photoactivity. Here, we directly explore the effect of the Y21 pKa on dark state recovery by replacing Y21 with fluorotyrosine analogues that increase the acidity of Y21 by 3.5 pH units. Ultrafast transient infrared measurements confirm that the structure of AppA is unperturbed by fluorotyrosine substitution, and that there is a small (3-fold) change in the photokinetics of the forward reaction over the fluorotyrosine series. However, reduction of 3.5 pH units in the pKa of Y21 increases the rate of dark state recovery by 4000-fold with a Brønsted coefficient of ∼ 1, indicating that the Y21 proton is completely transferred in the transition state leading from light to dark adapted AppA. A large solvent isotope effect of ∼ 6-8 is also observed on the rate of dark state recovery. These data establish that the acidity of Y21 is a crucial factor for stabilizing the light activated form of the protein, and have been used to propose a model for dark state recovery that will ultimately prove useful for tuning the properties of BLUF photosensors for optogenetic applications.